Fretting corrosion of screws contribute to the fixation failure of the femoral neck: a case report. Issue 4 (4th December 2019) - Luo, Jiajun; Ajami, Sara; Yu, Hai‐Ming; Ma, Shuanhong; Chen, Shen‐Mao; Zhou, Feng; Wang, Pei‐Wen; Yao, Xue‐Dong; Liu, Chaozong
Abstract : Fretting corrosion of metal implants has been associated with implant failure and revision surgeries. This report describes the fixation failure of a femoral neck fracture in a 61‐year‐old male patient due to corrosion of three cannulated screws. Radiographic evaluation at the time of primary surgery demonstrated well‐positioning of the cannulated screws. The patient had no significant medical comorbidities at the time of surgery. However, screw loosening and avascular necrosis were diagnosed after 5 years. At the revision surgery, inflammatory serological markers, C‐reactive protein and erythrocyte sedimentation rate showed no signs of infections, and screws were retrieved. Scanning electron microscopy observations showed that all screws were subjected to fretting corrosion which led to discolouration, pitting attack, and cracking. Thus, Fretting corrosion may have contributed to the failure of the fixation of screws.